The feminist revolution - Morris, Bonnie J., 1961-; Withers, D-M (Smithsonian Books, 2018)
"Explores the global history and contributions of the feminist revolution. The Feminist Revolution offers an overview of women's struggle for equal rights in the late twentieth century. Beginning with the auspicious founding of the National Organization for Women in 1966, at a time when women across the world were mobilizing individually and collectively in the fight to assert their independence and establish their rights in society, the book traces a path through political campaigns, protests, the formation of women's publishing houses and groundbreaking magazines, and other events that shaped women's history. It examines women's determination to free themselves from definition by male culture, wanting not only to "take back the night" but also to reclaim their bodies, their minds, and their cultural identity. It demonstrates as well that the feminist revolution was enacted by women from all backgrounds, of every color, and of all ages and that it took place in the home, in workplaces, and on the streets of every major town and city. This sweeping overview of the key decades in the feminist revolution also brings together for the first time many of these women's own unpublished stories, which together offer tribute to the daring, humor, and creative spirit of its participants"--